The Effect of Human Capital, Labors, and Capital on Economic Growth in Barlingmascakeb - Rizqia Mutiara Sani; Herman Sambodo; Bambang Bambang (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2018)
The economic growth of Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen regencies or known as Barlingmascakeb region is on average lower than the economic growth of Central Java Province. This study aims to analyze the influence of human capital that proxy from level of education and life expectacy, labor, and capital on economic growth in the Barlingmascakeb region. The data used is secondary data, time series starting from 2008-2015. This study uses multiple linear regression. Based on the results of the study it is known that the variable human capital, which is seen from the level of education and life expectancy, labor, capital has a positive influence on economic growth in the Barlingmascakeb region.Keywords: Level of Education, Life Expectancy, Labor, Capital, Economic Growth.